A Comprehensive Resiliency Framework: Theoretical Model, Treatment, and Evaluation - Elyse R Park PhD; Christina M Luberto PhD; Emma Chad-Friedman; Lara Traeger; Daniel L Hall PhD; Giselle K Perez PhD; Brett Goshe PhD; Ana-Maria Vranceanu PhD; Margaret Baim MS, ANP-BC; John W Denninger MD, PhD; Gregory Fricchione MD; Herbert Benson MD; et al. (SAGE Publishing, 2021)
Background There is heterogeneity in conceptualizations of resiliency, and there is, to date, no established theoretically driven resiliency assessment measure that aligns with a targeted resiliency intervention. We operationalize resiliency as one's ability to maintain adaptive functioning in response to the ongoing, chronic stress of daily living, and we use a novel resiliency measure that assesses the target components of an evidence based resiliency intervention. We present our resiliency theory, treatment model, and corresponding assessment measure (Current Experience Scale; CES). Methods To establish the psychometric properties of the CES, we report the factor structure and internal consistency reliability (N = 273). Among participants in our resiliency intervention (N = 151), we explored construct validity in terms of associations with theoretical model constructs, a validated resiliency measure, and sensitivity to change from before to after the intervention. Results Results indicated that a 23-item, 6-factor solution was a good fit to the data (RMSEA = .08, CFI = .97; TLI =.96) and internal consistency was good (α = .81 to .95). The CES showed correlations in the expected direction with resiliency model constructs (all p 's < .001) and significant post intervention improvements. Conclusion Our resiliency theory, treatment model, and outcome appear aligned; the CES demonstrated promise as a psychometrically sound outcome measure for our resiliency intervention and may be used in future longitudinal studies and resiliency building interventions to assess individuals' resiliency to adapt to ongoing stress.